The symbolism of the covid-19 event in the artwork of Issarezal Ismail - Siti Humaini Said Ahmad@Syed Ahmad (Tanjong Malim, 2022)
The symbolism of the covid-19 event in the artwork of Issarezal Ismail by Siti Humaini Said Ahmad@Syed Ahmad